The Epistemological Justification of Intercollegiate Advisement Programs for Student-Athletes or Why We Do What We Do in the First Place! - Pawlowski, Thomas F. (My University, 1985)
This is a short piece on the purpose behind why advisors support athletes at Union County College.
Keywords: ethics; academic support